On the properties of the Weibull-Burr III distribution and its application to uncensored and censored survival data - Aliyu Yakubu; Sani I. Doguwa (CBN Journal of Applied Statistics, 2017)
Twelve different families of cumulative distributions that are used to model real life data were introduced by Burr (1942). Burr III distribution is among these families of cumulative distributions. In this work, a four-parameter distribution is introduced to model real life scenarios called Weibull-Burr III distribution. The limiting behavior of the proposed distribution, hazard function, moments, skewness, kurtosis and quantile function is investigated; order statistics and entropy are also derived. The method of Maximum Likelihood Estimation technique was used in estimating the parameters of the proposed distribution. To prove the flexibility and performance of the distribution and Weibull-G family of distributions, censored and uncensored data sets are applied. The results suggest that the new compound distribution fit the real data and perform much better than its competitors for both censored and uncensored data.
Keywords: C02; C22; I10; 330; Rényi Entropy; Weibull-Burr type III Distribution; Weibull-G Family